A qualitative study of father involvement with their young children in mainland China - Liu, Yang; Guo, Mingchun; Dittman, Cassandra K.; Zheng, Ying; Haslam, Divna M. (Frontiers in Psychology, 2025)
IntroductionThe voices of Chinese fathers regarding their involvement with their young children remain largely absent in the existing research. Thus, it is critical to explore subjective experiences of and possible influences on Chinese fathers’ involvement with children from their point of view.MethodsThis study conducted semi-structured interviews with 35 Chinese fathers of preschoolers. Reflexive thematic analysis was used to analyze the interviews.ResultsChinese fathers both adhered to traditional paternal roles and increased proximity to their children while serving as maternal coparenting partners. Father involvement was related to intrapersonal, familial, and contextual factors. Intrapersonal factors included taking responsibility for being a father, optimizing children’s development and future, beliefs about parental roles, and fulfillment and joy versus tiredness and boredom. Familial factors include maternal availability for childcare and advocacy, the child’s requests and rejections, and the grandparent’s involvement and impediments to father involvement. Contextual factors include fathers’ occupational demands, networking demands, and invitations as well as opportunities for father involvement from school and community.DiscussionThe findings supported that multi-layered factors jointly influence how fathers are involved with their children. Yet, different from Western models of fathering focusing solely on child and mother characteristics, the role of grandparents was highlighted in Chinese fathers’ narratives, reflecting cultural influences on family dynamics. This highlights the need to consider the potential impact of grandparents in China and many other Asian countries, where multigenerational living is common. Additionally, the identified factors can guide the design of family programs and family-friendly policies to facilitate father involvement.